2012
DOI: 10.1007/s00248-012-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic and Eukaryotic Airborne Microorganisms as Tracers of Microclimatic Changes in the Underground (Postojna Cave, Slovenia)

Abstract: Bioaerosols in cave air can serve as natural tracers and, together with physical parameters, give a detailed view of conditions in the cave atmosphere and responses to climatic changes. Airborne microbes in the Postojna Cave system indicated very dynamic atmospheric conditions, especially in the transitory seasonal periods between winter and summer. Physical parameters of cave atmosphere explained the highest variance in structure of microbial community in the winter and in the summer. The airborne microbial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 29 publications
2
28
1
1
Order By: Relevance
“…Sampling was conducted deeper within the cave at Grotteà la Patate than at the other two sites, and this may explain the comparatively low fungal diversity. Other studies have found that fungal diversity decreases with increasing distance from cave entrances (Kuzmina et al, 2012;Mulec et al, 2012). Most of the fungal taxa documented during this study have previously been found in caves in other regions (Vanderwolf et al, 2013a).…”
Section: Discussionsupporting
confidence: 65%
“…Sampling was conducted deeper within the cave at Grotteà la Patate than at the other two sites, and this may explain the comparatively low fungal diversity. Other studies have found that fungal diversity decreases with increasing distance from cave entrances (Kuzmina et al, 2012;Mulec et al, 2012). Most of the fungal taxa documented during this study have previously been found in caves in other regions (Vanderwolf et al, 2013a).…”
Section: Discussionsupporting
confidence: 65%
“…There are different types of bioaerosol formation caused by wind, animals and humans, or splashing water (Mulec et al, 2012c). It occurs in natural and manmade environments.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and size of Postojna Cave, with its numerous known and unknown entrances at different levels and a long and highly ramified cave system, makes this cave a fascinating study site for a variety of physical and environmental studies (Bezek et al, 2012;Gosar et al, 2009;Kobal et al, 1988;Mulec et al, 2012;Šebela et al, 2010;Šebela and Turk, 2011;Vaupotič, 2008). In general the ventilation of Postojna Cave is characterised by convective airflow, controlled mainly by the temperature difference between the cave and the outside atmosphere, as discussed by for one measurement location in the Velika Gora (Great Mountain) chamber of Postojna Cave.…”
Section: Introductionmentioning
confidence: 99%